THE EFFECT OF LEARNING STYLES ON STUDENTS’ SENTENCE STRUCTURE ACHIEVEMENT - MARISI DEBORA (BAHAS, 2014)
This article presents the research findings of the effect of the students’ learning styles on their students’ sentence structure achievement. The study analyzed the students’ learning styles questionaires and their sentence structure test. It was found that students’ learning styles do not significantly affect their sentence structure achievement. It is concluded that although each student has his / her own characteristics that lead them into their own learning styles, they also have their own learning strategies, which facilitate learning task that help them to be a better language learner.